2004
DOI: 10.1037/h0087443
|View full text |Cite
|
Sign up to set email alerts
|

College Students' Memory for Vocabulary in Their Majors: Evidence for a Nonlinear Relation Between Knowledge and Memory.

Abstract: The effect of domain knowledge on students' memory for vocabulary terms was investigated. Participants were 142 college students (94 education majors and 48 business majors). The measure of domain knowledge was the number of courses completed in the major. Students recalled three different lists (control, education, and business) of 20 words. Knowledge effects were estimated controlling for academic aptitude, academic achievement, and general memory ability. Domain-specific knowledge consistently predicted rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In this study domain-specific prior knowledge was assessed in a way similar to that in other studies (cf. Alexander et al, 1994a , 1995 ; DeMarie et al, 2004 ; Levin and Arnold, 2004 ); since the method is appropriate there, non-significant correlations between some domains of prior knowledge and recall in this study might have other reasons which need to be considered. Perhaps the domains of prior knowledge differ in their distance to the topic.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In this study domain-specific prior knowledge was assessed in a way similar to that in other studies (cf. Alexander et al, 1994a , 1995 ; DeMarie et al, 2004 ; Levin and Arnold, 2004 ); since the method is appropriate there, non-significant correlations between some domains of prior knowledge and recall in this study might have other reasons which need to be considered. Perhaps the domains of prior knowledge differ in their distance to the topic.…”
Section: Discussionmentioning
confidence: 85%
“…Research on prior knowledge often is on mathematical or scientific topics (Alexander and Murphy, 1998 ; DeMarie et al, 2004 ). The advantage of investigating prior knowledge of such topics is that they are well-structured and clearly defined in terms of related topics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depth of topic knowledge and its relationship to vocabulary acquisition has been investigated in the native language and in general foreign language learning. De Marie et al (2004) found that native language vocabulary (English) learning could be predicted in university undergraduates by importance of vocabulary to their major area of study. De Marie et al noted that there was a threshold for predicting vocabulary acquisition and that a sufficient amount of coursework needed to be completed to have an effect.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of topic knowledge on the learning of domain-related vocabulary in the native language was studied directly by De Marie, Aloise-Young, Prideaux, Muransky-Doran, and Gerda (2004) in undergraduate education and business majors. Students were asked to recall three lists of 20 general, education, and business terms.…”
Section: Topic Knowledge and Expertisementioning
confidence: 99%